Post COVID-19 Syndrome Monitoring in Confirmed COVID-19 Patients with Telemedicine at Cipto Mangunkusumo Hospital - Yogi Prabowo; Ahmad Riza'i; Hadiki Habib; Radi Muharris Mulyana; Septo Sulistio; Imamul Aziz Albar; Lies Dina Liastuti; Sumariyono Sumariyono; Trimartani Trimartani; Muhammad Khalil Hasmarani; Muhammad Zuhdi (Interna Publishing, 2022)
Background: The incidence of post-covid-19 syndrome is quite high and requires further monitoring after the patient is discharged from treatment. So we need a proper monitoring method and description of the Covid-19 syndrome in Indonesia.  Methods: This retrospective cohort study with total sampling method uses data from medical records and telemedicine observations of confirmed COVID-19 patients who received treatment in the Kiara room at Cipto Mangunkusumo. The data were then analyzed using chi-squared and multinomial logistic regression techniques. Results: A total of 133 samples were used, including 44.4% male and 55.6% female, with an average age Standard Deviation (SD) of 40.36 (17.94). The severity levels of Covid-19 were mild (66.9%). The most common post-Covid-19 symptom manifestations was cough expressed at the first follow-up (first week after recovery) and second follow-up (the fourth week after recovery). Furthermore, the significant relationship between severity levels and post-Covid-19 symptomatic syndrome outcomes is the critical headache or vertigo symptoms with an RR of 8.70 (95% CI, 1.10-68.69,). In comparison, the telemedicine quality assessment was declared good, as shown by 98.7% of an examined sample. Conclusion: The most manifestation shown in the first and fourth week of follow-up is cough. Other symptoms tend to decrease in the second follow-up. The severity level associated with post-Covid-19 manifestations are severe-critical with headache or vertigo as a risk factor and mild with symptoms of headache or vertigo as a preventative. Meanwhile, the quality of telemedicine services was recognized as good by the majority of the sample.